2013
DOI: 10.1103/physrevb.88.140403
|View full text |Cite
|
Sign up to set email alerts
|

Role of magnetic chirality in polarization flip upon a commensurate-incommensurate magnetic phase transition in YMn2O5

Abstract: We have performed simultaneous measurements of magnetic chirality by using polarized neutrons and electric polarization along the b-axis of single crystals of YMn 4+ (Mn1−xGax) 3+ O5 with x = 0.047 and 0.12, in which nonmagnetic Ga-ions dilute Mn 3+ spins. The x = 0.047 sample exhibits high-temperature incommensurate (HT-ICM), commensurate (CM), and low-temperature incommensurate (LT-ICM) magnetic phases in order of decreasing temperature, whereas the x = 0.12 sample exhibits only HT-ICM and LT-ICM phases. Her… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 24 publications
2
23
1
Order By: Relevance
“…45 The reduction of the polarization and the sign reversal in YMn 2 O 5 was suggested to originate from a competition of two contributions to the ferroelectric polarization, one arising from the exchange striction mechanism which involves the Mn 4+ -Mn 3+ chains (dominating in the high-temperature commensurate phase) and a second contribution due to the cycloidal spin modulation of Mn 4+ moments along the c-axis. 46,47 The question whether or not the same mechanism could explain the pressure-induced FE2 phase in GdMn 2 O 5 needs to be discussed in more detail.…”
Section: Discussionmentioning
confidence: 99%
“…45 The reduction of the polarization and the sign reversal in YMn 2 O 5 was suggested to originate from a competition of two contributions to the ferroelectric polarization, one arising from the exchange striction mechanism which involves the Mn 4+ -Mn 3+ chains (dominating in the high-temperature commensurate phase) and a second contribution due to the cycloidal spin modulation of Mn 4+ moments along the c-axis. 46,47 The question whether or not the same mechanism could explain the pressure-induced FE2 phase in GdMn 2 O 5 needs to be discussed in more detail.…”
Section: Discussionmentioning
confidence: 99%
“…Second, it is noted that all these data were obtained in single crystal samples grown by flux method. These single crystals are claimed to have strong self-polarized effect which would self-polarize the FE domains3233, leading to the strong path-relevance of the measured data. This consequence was often mentioned in literature on RMn 2 O 5 3335 to account for those anomalous data on polarization below T N2 .…”
mentioning
confidence: 97%
“…The two cases, taking R = Tm and R = Y, are plotted in Fig. 1(b,c) for a guide of eyes3133. It has been suggested that component P C is related to the symmetric exchange striction, i.e.…”
mentioning
confidence: 99%
“…Wakimoto et al 107 selectively replaced Mn 3 þ in the host lattice by Ga 3 þ , disrupting the AFM zig-zag chain and destroying the CM order for 12% substitution. However, they did observe a polarization below 20 K, where the cycloidal spin phase appears.…”
Section: Symmetric Exchange Strictionmentioning
confidence: 99%
“…Figure 6. 107 The improper ferroelectricity in the collinear (CM) phase can be explained in terms of symmetric exchange striction effects. 102 A magnetically frustrated spin chain runs along the b axis and consists of pairs of almost parallel and antiparallel Mn 3 þ and Mn 4 þ spins with ↑↑↓↑ order, as shown schematically in the central panel of Figure 6.…”
Section: Ferroaxial Multiferroics (Camn 7 O 12 )mentioning
confidence: 99%